DEVELOPING THE GAME MASTER OF MATHLAND TO INCREASE PROBLEM-SOLVING FOR GRADE FOUR OF ELEMENTARY - Any Widyasari; Juneau, Janelle L. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Practicing problem-solving in mathematics is key to understanding word problems and solving real-life situations. This study aims to develop a board game, called “Master of Mathland”, for grade four elementary students using basic operations by assessing its effectiveness, validity, and practicality to increase students’ problem-solving. This research was conducted in grade four of SDN Tanjung 01, Central Java, using the Borg Gall et al research and development method through the six steps, combined with the ADDIE development model. The data was gathered through observation, interviews, questionnaires, tests, and documentation. The product validity results from the media expert is 92,39%, categorized “Highly Valid” and the material expert is 94,32, categorized “Highly Valid”. Besides, the teacher’s response sheet for the practical test is 79,00% stated “Advantageous” for learning. The effectiveness of the media is “Very Effective” with 90,36%, through the student's response sheet. The product's effectiveness in increasing problem-solving was tested through the Wilcoxon T-Test, resulting in Asymp.Sig. (2-tailed) is 0.00, meaning the product increases problem-solving in grade four of elementary. Therefore, the game “Master of Mathland” is valid, advantageous, effective, and can improve grade four students’ problem-solving.